PROFILE OF STUDENT’S CONCEPT UNDERSTANDING IN COMPARATIVE MATERIAL WITH VALUE AND VARIOUS GRADES IN CLASS VII - Ni Luh Regita Eka Widhiani; Anggraini Anggraini; Gandung Sugita; Ibnu Hajar (USN Kolaka, 2023)
Students' understanding of concepts needs to be profiled so that teachers can find out the description and understanding of students' mathematical conceptsThis study aims to obtain a description or description of students' understanding of the concept of value comparison material and value turning at SMP Negeri 1 Ampibabo. This type of research is descriptive with a qualitative approach. The subjects of this study were students of class VII A at SMP Negeri 1 Ampibabo, which consisted of one student each with high, medium, and low mathematical abilities and good communication skills according to the teacher's recommendations. The results of this study are that students with high mathematical abilities are able to use the four indicators to understand the concept, and students with moderate mathematical abilities are able to use the four indicators to understand the concept. However, they are still mistaken in distinguishing comparisons of equivalent and reverse values, and students with low mathematical abilities are only able to use three indicators of conceptual understanding in working on comparison questions of value and return value.